Sasando as a Symbol of Cultural Identity of the Rote Island Community and the Challenges of Preserving - Natonis, Rolfi Junyanto Is; Jazuli, Muhammad; Utomo, Udi; Widodo, Widodo; Narselina, Puput Meinis (Resital: Jurnal Seni Pertunjukan, 2025)
This research examines Sasando as a symbol of cultural identity and pride of the people of Rote Island by exploring its philosophical values, social functions, and the challenges of its preservation in the midst of modernization. The present study employed a qualitative case study approach, with data collected through participatory observation and in-depth interviews with Sasando players, craftsmen, and cultural figures. The research findings reveal three key aspects: the value of cultural identity reflected in the use of natural materials (bamboo and palm) and its role in traditional rituals as a marker of local wisdom, social function as a medium of community unification in collaborative events and a means of intergenerational value transmission, and preservation challenges in the form of declining interest from the younger generation, lack of integration in formal education, and limited promotion. The research also identified opportunities through cultural festivals and tourism-based economic potential. The research conclusions emphasize that Sasando is not merely a musical instrument, but rather a symbol of collective identity that represents the history, social values, and cultural resilience of the Rote people. The following policy recommendations are put forth: first, the integration of a Sasando-based curriculum; second, the strengthening of youth training programs; and third, multi-stakeholder collaboration for sustainable promotion strategies. This research makes a theoretical contribution to the discussion of the relationship between traditional musical instruments, identity construction, and cultural preservation strategies in the midst of globalization.